2006
DOI: 10.1111/j.1467-7687.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual development of infants, children and adolescents with congenital heart disease

Abstract: Cardiac disease is the most common congenital defect in children, affecting between 3 and 10 in every 1000 live births. While significant advances in medical and surgical management have resulted in increasing numbers of survivors, it is also recognized that there is a growing population of children living with neurological impairment and lowered intellectual function. The aetiology of such impairment is multi-factorial and hypoxia is one of the factors involved. This article provides an overview of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 98 publications
1
24
0
1
Order By: Relevance
“…Although mortality due to CHD continues to decline (Boneva et al, 2001), infants surviving the immediate neonatal period are at increased risk for significant acute and chronic morbidities including NEC (Ades et al, 2005;Brown et al, 2005;Laussen, 2001;McElhinney et al, 2000) and impaired neurodevelopmental outcomes (Brown et al, 2005;Laussen, 2001;Wernovsky, 2006;Wray, 2006). Advances in palliative and reparative procedures have lead to a substantial decrease in mortality such that associated morbidities are now the most reliable outcome measures by which to compare new approaches and therapies (Laussen, 2001).…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Although mortality due to CHD continues to decline (Boneva et al, 2001), infants surviving the immediate neonatal period are at increased risk for significant acute and chronic morbidities including NEC (Ades et al, 2005;Brown et al, 2005;Laussen, 2001;McElhinney et al, 2000) and impaired neurodevelopmental outcomes (Brown et al, 2005;Laussen, 2001;Wernovsky, 2006;Wray, 2006). Advances in palliative and reparative procedures have lead to a substantial decrease in mortality such that associated morbidities are now the most reliable outcome measures by which to compare new approaches and therapies (Laussen, 2001).…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Previous studies have examined the cognitive development of children with CHD and the cognitive effects of medical and surgical treatment for the cardiac disease (Daliento, Mapelli, & Volpe, 2006;HĂŒ lser et al, 2007). It has been suggested that many children with cardiac disease require a considerable amount of school support because of learning difficulties (Wray, 2006). Parents of children with CHD have reported lower school results and more school problems than parents of healthy children (Miatton et al, 2007;Walker, Gauvreau, & Jenkins, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in surgical and medical care have led to dramatic increases in survival rates, as over one million adults now have some form of CHD (Sable et al, 2011; Warnes et al, 2008). But much like children with a range of chronic systemic health conditions including sickle cell disease and diabetes (Berkelhammer et al, 2007; Desrocher & Rovet, 2004), CHD, as well as related cyanosis and early cardiac surgery, often has significant adverse effects on brain development and neurocognitive function (Wray, 2006). Emerging evidence suggests that as children with CHD grow into adolescence and young adulthood, they may be at risk for long-term neuropsychological consequences (Marino et al, 2012).…”
mentioning
confidence: 99%